Native Hawaiian and Pacific Islander populations in genomic research - Edra K. Ha; Daniel Shriner; Shawneequa L. Callier; Lorinda Riley; Adebowale A. Adeyemo; Charles N. Rotimi; Amy R. Bentley (npj Genomic Medicine, 2024)
Abstract The role of genomic research and medicine in improving health continues to grow significantly, highlighting the need for increased equitable inclusion of diverse populations in genomics. Native Hawaiian and Pacific Islander (NHPI) communities are often missing from these efforts to ensure that the benefits of genomics are accessible to all individuals. In this article, we analyze the qualities of NHPI populations relevant to their inclusion in genomic research and investigate their current representation using data from the genome-wide association studies (GWAS) catalog. A discussion of the barriers NHPI experience regarding participating in research and recommendations to improve NHPI representation in genomic research are also included.